Pengaruh Brand Ambassador Terhadap Keputusan Pembeli (Di Platform E-Commerce Shopee Dan Tokopedia) - Angelina Elvina; Ngajudin Nugroho; Fauzi Akbar Maulana Hutabarat; Ivone Ivone; Elserra Siemin Ciamas (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The purpose of this study is to determine (1) the influence of brand ambassadors on buyer decisions on the shopee platform. (2) the influence of brand ambassadors on buyer decisions on the Tokopedia platform. (3) to compare the influence of brand ambassadors on buyer decisions on the shopee and tokopedia platforms. The research method used is a comparative quantitative research method, the number of samples processed is 45 respondents, the sample collection technique uses incidental sampling and the sampling technique uses a questionnaire which is processed using Data Processing Software. Based on the linearity test on the shopee and Tokopedia respondents' data, there is a linear relationship between the brand ambassador variable and the purchasing decision variable. Based on the results of the correlation test, shopee has a brand ambassador relationship and the buyer's decision is positive, strong and unidirectional. Results sig. (2-tailed) obtained is 0.02 < 0.05. Tokopedia correlation test has a relationship between brand ambassador and buyer's decision is positive, strong and unidirectional. Results sig. (2-tailed) obtained is 0.01 < 0.05. Based on the coefficient of determination of shopee respondents' data, the influence of brand ambassadors on buyer decisions is 31.4% while the influence of brand ambassadors on buyer decisions at Tokopedia is 53.9%. Based on the results of simple linear regression shopee shows the value of sig. 0.002≤0.05 so that it has an influence on shopee data, while Tokopedia data shows a sig value. 0.001≤0.05 which can be interpreted as having an influence between brand ambassadors on purchasing decisions. The results of the t-test (hypothesis) on the shopee respondent's data tcount < ttable or (3.451>2.060) with a sig value of 0.02. Meanwhile, in Tokopedia, tcount > ttable (4,190 > 2,145) with a sig value of 0.01